Evaluation of energy metabolism in septic patients with and without AKI - Sanches, Ana Cláudia Soncini [UNESP]; de Góes, Cassiana Regina [UNESP]; Bufarah, Marina Nogueira Berbel [UNESP]; de Oliveira, Mariana Cassani [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (Springer Nature, 2017)
Background: The determination of resting energy expenditure (REE) in critically ill patients could prevent complications such as hypo- and hyperalimentation. This study aims to describe the REE in septic patients with and without acute kidney injury (AKI) and compare the REE estimated by the Harris-Benedict equation (HB) with the REE measured by indirect calorimetry (IC). Methods: Prospective and observational study was performed. Septic patients older than 18 years, undergoing mechanical ventilation, with or without AKI defined by KDIGO criteria, and admitted to the Intensive Care Unit of University Hospital from Brazil were included. The REE was estimated by HB equation and measured by the IC within 72 h after the diagnosis of sepsis and 7 days after the initial measure. Results: Sixty-eight patients were evaluated, age was 62.5 ± 16.6 years, 64.7% were male, 63.2% had AKI, and SOFA was 9.8 ± 2.35. The measured REE was 1857.5 ± 685.32 kcal, while the estimated REE was 1514.8 ± 356.72 kcal, with adequacy of 123.5 ± 43%. Septic patients without AKI (n = 25) and with AKI (n = 43) had measured REE statistically higher than the estimated one (1855.0 (1631.75–2052.75) vs. 1551.0 kcal (1349.0–1719.25), p = 0.007 and 1868.0 (1219.5–2364.75) vs. 1388.0 kcal (1254.0–1665.5), p = 0.026, respectively). There was no significant difference between the two groups (with and without AKI) in measured and estimated REE (p = 0.63 and 0.64, respectively). There was no significant difference in evolutional REE (1845.95 ± 658.27 kcal vs. 1809.54 ± 755.08 kcal, p = 0.86). Conclusions: The REE measured by IC was significantly higher than that estimated by HB equation in both septic with and without AKI. There was no significant difference in REE between the septic patients with and without AKI, suggesting that AKI does not influence the energy metabolism of septic patients.
Keywords: Acute kidney injury; Energy expenditure; Sepsis